Green synthesis and characterization of palladium nanoparticles and its conjugates from solanum trilobatum leaf extract - Kanchana, Amarnath; Devarajan, Saveetha; Ayyappan, Senniyanallur Rathakrishnan (Nano-Micro Letters, 2010)
An important area of research in nanotechnology deals with the synthesis of nanoparticles of different chemical compositions, sizes and controlled monodispersity. Currently, there is a growing need to develop environmentally benign nanoparticle synthesis in which no toxic chemicals are used in the synthesis protocol. Palladium nanoparticles (PdNp) are of interest because of their catalytic properties and affinity for hydrogen. Our protocol for the phyto-synthesis of PdNp under moderate pH and room temperature offers a new means to develop environmentally benign nanoparticles. Solanum trilobatum is enlightened in our present study as it is enriched with phytochemicals to reduce palladium chloride ions. Poly MVA a dietary supplement based on the nontoxic chemotherapeutic lipoic acid-palladium complex (LA-Pd) is been hypothesized as the new paradigm of cancer therapy. Hence forth we successfully conjugated lipoic acid (S-PdNp-LA) and vitamins (S-PdNp-Vitamin-LA) to palladium nanoparticles synthesised from Solanum trilobatum leaf extract. These nanoparticles (S-PdNp, S-PdNp-LA, S-PdNp-Vitamin-LA) were characterized with UV-Vis Spectroscopy, SEM and FTIR analysis, which revealed that S-PdNp are polydisperse and of different morphologies ranging from 60∼70 nm (S-PdNp), 65∼80 nm (S-PdNp-LA) and 75∼100 nm (S-PdNp-Vitamin-LA) in size.